Effect of Functionalized Carbon Nanotubes in the Detection of Benzene at Room Temperature - Nurjahirah Janudin; Norli Abdullah; Wan Md Zin Wan Yunus; Faizah Md Yasin; Mohd Hanif Yaacob; Norshafiqah Mohamad Saidi; Noor Azilah Mohd Kasim (Journal of Nanotechnology)
In this paper, carbon nanotubes (CNTs) were functionalized by acid treatment and further functionalized with dodecylamine and were designated as CNT-carboxylic and CNT-amide, respectively. Then, functionalized CNTs produced were characterized with various methods to verify the attachment of a functional group. Performance of the functionalized CNTs in the detection of benzene gas was monitored at room temperature. The sample was dropped cast on the interdigitated transducer (IDT), and the changes in resistivity were recorded by a digital multimeter in a customized chamber under controlled humidity (∼55%) environment. Based on the findings, it showed that the functionalized CNTs provide an extra active area for interaction between the gas analyte and CNTs, thus increasing their response and improving the sensitivity of the sensing material.